Functional properties and in vitro antioxidant and antibacterial effectiveness of pigskin gelatin films incorporated with hydrolysable chestnut tannin. (April 2015) - Peña-Rodriguez, Cristina; Martucci, Josefa F; Neira, Laura M; Arbelaiz, Aitor; Eceiza, Arantxa; Ruseckaite, Roxana A
The impact of the incorporation of 10% w/w of hydrolyzable chestnut tannin into pigskin gelatin (G) films plasticized with glycerol (Gly) on the physicochemical properties as well as the in vitro antioxidant and antibacterial effectiveness against food-borne pathogens such as Escherichia coli and Streptococcus aureus was investigated. A higher tendency to both redness (a*) and yellowness (b*) coloration characterized gelatin films incorporated with chestnut tannin. The reduced lightness (L) and transparency of gelatin–chestnut tannin films plasticized with 30% w/w Gly might be associated with certain degree of phase separation which provoked the migration of the plasticizer to the film surface. The incorporation of chestnut tannin and glycerol affected the chemical structure of the resultant films due to the establishment of hydrogen interactions between components as revealed by Fourier transform infrared spectroscopy. These interactions reduced gelatin crystallinity and seemed to be involved in the substantial decrease of the water uptake of films with tannin, irrespective of the glycerol level. Such interactions had minor effect on tensile properties being similar to those of the control films (without chestnut tannin) at the same glycerol level. Films modified with 10% w/w chestnut tannin showed significant (P < 0.05) 2, 2-diphenyl-1-picrylhydrazyl radical scavenging activity, ca. from 0 ± 0.033 to 87.1 ± 0.002% for chestnut tannin-free and chestnut tannin-containing gelatin films. The limited inhibitory activity of films incorporated with 10% w/w chestnut tannin against the selected bacteria evidenced by disk diffusion method probably resulted from the interactions within the film restricting the diffusion of the active agent into the agar medium. The more modest protective effect observed against a Gram-positive bacterium ( S. aureus ) was also discussed.